Design and pre-flight performance of SPIDER 280 GHz receivers - Shaw, E.C.; Ade, P.A.R.; Akers, S.; Amiri, M.; Austermann, J.E.; Beall, J.A.; Becker, D.T.; Benton, S.J.; Bergman, A.S.; Bock, J.J.; Bond, J.R.; Bryan, S.A.; et al. (Millimeter, Submillimeter, and Far-Infrared Detectors and Instrumentation for Astronomy X, 2020)
International audience In this work we describe upgrades to the Spider balloon-borne telescope in preparation for its second flight, currently planned for December 2021. The Spider instrument is optimized to search for a primordial B-mode polarization signature in the cosmic microwave background at degree angular scales. During its first flight in 2015, Spider mapped ~10% of the sky at 95 and 150 GHz. The payload for the second Antarctic flight will incorporate three new 280 GHz receivers alongside three refurbished 95- and 150 GHz receivers from Spider's first flight. In this work we discuss the design and characterization of these new receivers, which employ over 1500 feedhorn-coupled transition-edge sensors. We describe pre-flight laboratory measurements of detector properties, and the optical performance of completed receivers. These receivers will map a wide area of the sky at 280 GHz, providing new information on polarized Galactic dust emission that will help to separate it from the cosmological signal.